SOCIAL CHANGE IN SELF-PERCEPTIONS OF AGING ACROSS TWO DECADES - Wurm, S (Innov Aging, 2018)
Recent studies point to social change of age stereotypes and their increasing negativity during the last decades. This has recently been described as paradox because of improved living situations of older adults. However, self-perceptions of aging (SPA) do not need to follow the same trend as age stereotypes, in particular in older adults. This study examines social change in SPA from 1996 to 2014. Data come from four independent, cross-sectional waves of the German Ageing Survey (DEAS). The sample consists of n = 19,826 participants (40–83 y.). Findings point to diverging trends in middle adulthood and old age. For individuals aged 66 or older, SPA have changed to the positive. In middle adulthood, a tendency towards more negative SPA is observed. Whereas social change of SPA in older adults might reflect improved living situations in later life, findings for middle-aged adults rather support findings of increasing negativity of age stereotypes.